Pengembangan Tanaman Sela di Bawah Tegakan Tanaman Tahunan - Didy Sopandie; Trikoesoemaningtyas Trikoesoemaningtyas (Puslitbang Tanaman Pangan, 2011)
Development of Crops Variety Tolerant to Low-light Intensity for Intercropping. The effort to increased food crops production is limited by the lack of arable land. Therefore, there is a need to utilize marginal areas such as land under estate crops which is partly shaded and hence have low light intensity as well as high acidity and drought condition. Production increase is marginal areas, such as lands under canopies of estate crops, could be achieved by improvement in (1) crop adaptation to abiotic stresses and resistance to biotic stress, (2) yield potential, and (3) cultural techniques which are based on knowledge in plant physiology and ecophysiology. A collaborative research on plant physiology, molecular biology and plant breeding is affected to be able to create approviate technologies to overcome those problems. Food crops which are potential to be produced under shaded condition as intercrops are upland rice, soybean, taro, elephant foot yams, and legume crops. Plant adaptation to low-light intensity is achieved through efficiency in light interception (avoidance) and utilization (tolerance). Through integrated research of interdisciplinary approach several promising lines of soybean having high productivity under 50% shading were selected.